Influence of oceanography on bowhead whale (Balaena mysticetus) foraging in the Chukchi Sea as inferred from animal-borne instrumentation - Citta, J.J.; Olnes, J.; Okkonen, S.R.; Quakenbush, L.; George, J.C.; Maslowski, Wieslaw; Osinski, R.; Heide-Jørgensen, M.P. (Elsevier, 2021)
17 USC 105 interim-entered record; under review. The article of record as published may be found at https://doi.org/10.1016/j.csr.2021.104434 The distribution of the Bering-Chukchi-Beaufort Sea population of bowhead whales (Balaena mysticetus) is largely centered in the Chukchi Sea in autumn (September–November), which is also when sea ice is at minimum extent allowing for increased ship traffic and industrial activity. Prior work paired autumn movements of bowhead whales in the Chukchi Sea with simulated hydrographic information and concluded whales followed relatively cold, saline waters of Pacific origin during migration (<0 ◦C, 31.5–34.25 psu). We attached six Satellite Relay Data Logger (SRDLs) that included miniaturized Conductivity, Temperature, and Depth (CTD) sensors capable of collecting temperature (T) and salinity (S) profiles as whales dove, allowing us to verify and expand upon prior habitat studies. Areas where transiting whales stopped and lingered (presumably to feed) were associated with colder surface temperatures and lingering behavior peaked where seafloor salinity was ~33 psu. Whales were also more likely to linger in areas where density gradients were lower at the seafloor. Whales targeted colder, more saline waters of Pacific origin, in agreement with our prior work. Surface and dive behavior of whales tagged in this and other studies suggests that most feeding in the central Chukchi Sea is occurring at depths below the surface, and that surface temperature is indicative of (a proxy for) other processes occurring at depth. We suggest that colder surface temperatures are indicative of the main pathway(s) by which zooplankton are advected through the Chukchi Sea. However, because similar movement patterns in other stocks of bowhead whales have been interpreted as the avoidance of thermal stress, we suggest more research is needed on thermoregulation before this question can be resolved. Global Model Analysis program Department of Energy Regional Office of Naval Research Arctic ...